Parameterizing the Impact of Unresolved Temperature Variability on the Large‐Scale Density Field: 2. Modeling. (5th March 2022) - Kenigson, J. S.; Adcroft, A.; Bachman, S. D.; Castruccio, F.; Grooms, I.; Pegion, P.; Stanley, Z.
Abstract: Ocean circulation models have systematic errors in large‐scale horizontal density gradients due to estimating the grid‐cell‐mean density by applying the nonlinear seawater equation of state to the grid‐cell‐mean water properties. In frontal regions where unresolved subgrid‐scale (SGS) fluctuations are significant, dynamically relevant errors in the representation of current systems can result. A previous study developed a novel and computationally efficient parameterization of the unresolved SGS temperature variance and resulting density correction. This parameterization was empirically validated but not tested in an ocean model. In this study, we implement deterministic and stochastic variants of this parameterization in the pressure‐gradient force term of a coupled ocean‐sea ice configuration of the community Earth system model‐modular ocean model version 6 and perform a suite of hindcast sensitivity experiments to investigate the ocean response. The parameterization leads to coherent changes in the large‐scale ocean circulation and hydrography, particularly in the Nordic Seas and Labrador Sea, which are attributable in large part to changes in the seasonally varying upper‐ocean exchange through Denmark Strait. In addition, the separated Gulf Stream strengthens and shifts equatorward, reducing a common bias in coarse‐resolution ocean models. The ocean response to the deterministic and stochastic variants of the parameterization is qualitatively, albeit not quantitatively, similar, yet qualitative differences are found in various regions. Plain Language Summary: In ocean models, the location and strength of current systems are related to horizontal gradients of the seawater density. The density of seawater is calculated using an equation of state which depends on the temperature and salinity. These water properties could vary considerably over the spatial scale of one model grid box, yet ocean models resolve only grid‐cell‐mean water properties. As the seawater equation of state is nonlinear, density gradients which are calculated by applying this equation to the grid‐cell‐mean water properties could contain errors which result in the misrepresentation of current systems. Therefore, parameterizations have been developed to represent the unknown subgrid‐scale water property variance in terms of resolved variables, allowing for a correction to the resolved density field. In this study, we implement and test a parameterized density correction in a coupled ocean‐sea ice configuration of the community Earth system model‐modular ocean model version 6. The ocean response to the density correction consists of large‐scale circulation changes, particularly in the Atlantic Ocean. The representation of the Gulf Stream, a dynamically important current for the global ocean circulation, is found to improve. Key Points: Coarse‐resolution ocean model density fields contain systematic errors due to subgrid‐scale variance Parameterizations of density correction cause circulation changes in the North and South Atlantic Ocean Parameterizations reduce coarse‐resolution model biases in the Gulf Stream representation